2015
DOI: 10.5301/tj.5000210
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of Bevacizumab Concomitantly Administered with Carboplatin versus Carboplatin Alone in Patients with Recurrent Glioblastomas

Abstract: The combination of BEV and CBDCA is associated with improved response rates and survival compared with CBDCA alone. These results highlight the value of BEV in recurrent GBM. However, the clinical benefit of this interesting approach needs validation in a larger patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additional agents used against GBM include other nitrosoureas such as fotemustine, which can be administered as a single agent or in combination with PCV (P: procarbazine, C: lomustine and V: vincristine). Carboplatin, etoposide and irinotecan are other regimens that have shown modest efficacy after single or combined administration [ 37 ]. Clinical trials with cediranib, gefitinib and erlotinib for recurrent GBM have not shown an improvement in prolonging survival so far [ 38 , 39 , 40 ].…”
Section: Newly Diagnosed and Recurrent Gbm: Treatment And Managementmentioning
confidence: 99%
“…Additional agents used against GBM include other nitrosoureas such as fotemustine, which can be administered as a single agent or in combination with PCV (P: procarbazine, C: lomustine and V: vincristine). Carboplatin, etoposide and irinotecan are other regimens that have shown modest efficacy after single or combined administration [ 37 ]. Clinical trials with cediranib, gefitinib and erlotinib for recurrent GBM have not shown an improvement in prolonging survival so far [ 38 , 39 , 40 ].…”
Section: Newly Diagnosed and Recurrent Gbm: Treatment And Managementmentioning
confidence: 99%